2015
DOI: 10.1097/shk.0000000000000228
|View full text |Cite
|
Sign up to set email alerts
|

Electroporation-Mediated Gene Delivery of Na+,K+-ATPase, and ENaC Subunits to the Lung Attenuates Acute Respiratory Distress Syndrome in a Two-Hit Porcine Model

Abstract: Introduction Acute Respiratory Distress Syndrome (ARDS) is a common cause of organ failure with an associated mortality rate of 40%. The initiating event is disruption of alveolar-capillary interface causing leakage of edema into alveoli. Hypothesis: Electroporation mediated gene delivery of epithelial sodium channel (ENaC) and Na+,K+-ATPase into alveolar cells would improve alveolar clearance of edema and attenuate ARDS. Methods Pigs were anesthetized, instrumented, and the superior mesenteric artery was cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…51 This strategy appears to be a safe means of transferring genetic material to healthy lungs, and may be efficacious even in setting of acute and severe lung disease. 52, 53 …”
Section: Discussionmentioning
confidence: 99%
“…51 This strategy appears to be a safe means of transferring genetic material to healthy lungs, and may be efficacious even in setting of acute and severe lung disease. 52, 53 …”
Section: Discussionmentioning
confidence: 99%
“…A second advantage is that its activity is only limited to the area of electrical field, thus avoiding potential systemic effects derived from vector dissemination. Studies from the laboratory of David Dean have demonstrated the applicability of this method of gene delivery in large animal models such as swine (37). The amount of energy used has been calculated in 0.2 joules/kg, much less than defibrillators in hospital practice (38).…”
Section: Discussionmentioning
confidence: 99%
“…While these plate electrodes are rather small using electrode surface areas of less than 1 cm 2 , larger plate electrodes can also be used safely for electroporation of larger organs or animals. For example, we have used defibrillation paddles and defibrillation electrode pads (10 × 15 cm) to deliver fields across the chests of 40-kg pigs for efficient gene delivery into the lungs (Dean, Barravecchia, Danziger, & Lin, 2011; Emr et al, in press). …”
Section: Electrodesmentioning
confidence: 99%